2015
DOI: 10.1002/ase.1546
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of a short interprofessional education interaction between medical and physical therapy students

Abstract: Medicine is increasingly focused on team-based practice as interprofessional cooperation leads to better patient care. Thus, it is necessary to teach teamwork and collaboration with other health care professionals in undergraduate medical education to ensure that trainees entering the workforce are prepared to work in teams. Gross anatomy provides an opportunity to expose students to interprofessional education (IPE) early in their training. The purpose of this study is to describe an IPE experience and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…The researchers found that the nursing students had significantly higher scores on the domain of roles and responsibilities attributing this increase to the greater clinical exposure and additional IPE experiences. Likewise, Systma, et al [18] found significant differences in the roles and responsibility domain between medical students and physical therapy students in an anatomy lab with medical students scoring significantly higher that the physical therapy students. A study by Rose, et al [24]with similar disciplines as represented in this study did not show differences amongst the disciplines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The researchers found that the nursing students had significantly higher scores on the domain of roles and responsibilities attributing this increase to the greater clinical exposure and additional IPE experiences. Likewise, Systma, et al [18] found significant differences in the roles and responsibility domain between medical students and physical therapy students in an anatomy lab with medical students scoring significantly higher that the physical therapy students. A study by Rose, et al [24]with similar disciplines as represented in this study did not show differences amongst the disciplines.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, many healthcare educational programs lack adequate opportunities and training in IPE [18]. Mellor, Cottrell, and Moran [19] (conducted semi-structured interviews with students following an IPE program offered four times to students in medicine, physical therapy, occupational therapy, pharmacy, and nursing.…”
Section: Introductionmentioning
confidence: 99%
“…IPE enables the sharing of skills and knowledge among health care professions and promotes better understanding, shared values, and respect for the roles of other health care professionals 32 – 34 . In countries such as the U.S., UK, Sweden, Canada, and Italy, IPE has been developed as a means of improving collaboration between health care and social work professionals 3 , 8 , 20 , 23 , 24 , 26 , 30 , 33 . The Centre for the Advancement of Interprofessional Education defines IPE as a teaching and learning process that fosters collaborative work between two or more professions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we assessed 16 studies that examined the effects of IPE on health professions students’ education and attitude differences by gender and profession. Most of these studies found that IPE learning had a positive effect on students’ understanding of collaboration and attitudes about interprofessional teamwork 3 , 20 22 , 24 , 26 , 30 , 36 , 37 . However, two studies concluded that IPE learning had no effect 18 or a negative effect 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Die Modelle veranschaulichen, wie facettenreich sich interprofessionelle Zusammenarbeit in der Praxis darstellt und wie komplex die Anforderungen an die Mitglieder des interprofessionellen Teams sind. International empfehlen daher viele Forscher/-innen eine Schulung der Gesundheitsfachkräfte in der interprofessionellen Zusammenarbeit, um im Praxisalltag erfolgreich in interprofessionellen Teams arbeiten zu können (Arfons et al, 2015;Herrmann et al, 2015;Sytsma et al, 2015). Eine interprofessionelle Ausbildung der Gesundheitsberufe gilt als innovative Strategie, um die Zusammenarbeit der Gesundheitsberufe zu fördern, dadurch das Gesundheitssystem zu stärken und bessere Ergebnisse an Patienten/-innen zu erzielen (WHO, 2010).…”
unclassified